تأثير إضافة هيومات البوتاسيوم عند مستويات مختلفة من الشد الرطوبي في بعض الخواص الفيزيائية للتربة وفي نمو نبات الذرة الصفراء (zea maize) (Latakia University Journal -Biological Sciences Series, 2019)
أجري البحث لدراسة تأثير إضافة مستويات مختلفة من هيومات البوتاسيوم POWHUMUS WSG 85 (0.6-1.8-3.6 كغ/ دونم) عند مستويات مختلفة من الشد الرطوبي (400-600-800 ميلليبار) في خصائص التربة الفيزيائية وفي نمو نبات الذرة الصفراء على تربة طينية سلتية. تبين النتائج انخفاض الكثافة الظاهرية للتربة عند الشد الرطوبي 400 ميلليبار بشكل معنوي عند جميع مستويات الإضافة من هيومات البوتاسيوم بمقدار 0.05-0.1-0.17 غ/سم3 على التوالي، ومع زيادة الشد الرطوبي إلى 600 و800 فقد انخفضت الكثافة في المعاملة بدون إضافة هيومات البوتاسيوم بمقدار 0.08 -0.13غ/سم3 مقارنة بمستوى الشد 400 ميلليبار. كما تبين النتائج أن الثوابت التجريبية (a,b) في العلاقة ψ=aθb بين الشد الرطوبي والرطوبة الحجمية تزداد مع زيادة معدل الإضافة من الهيومات عند جميع مستويات الشد الرطوبي وأن معامل التوصيل المشبع زاد معنوياً بمقدار 2.71 م/يوم عند شد رطوبي 400 ميلليبار ومستوى إضافة 3.6 كغ هيومات/دونم، وبمقدار 4.17 م/يوم عند شد رطوبي  800ميلليبار ومستوى إضافة  3.6 كغ هيومات/دونم. لقد زادت نسبة الماء المتاح في التربة عند مستوى الإضافة 3.6 كغ هيومات/دونم بمقدار 5.47-5.33-5.14% على التوالي عند مستويات الشد الرطوبي (400-600-800 ميلليبار) مقارنة بالمعاملات لذات الشد الرطوبي وبدون إضافة الهيومات. وأظهرت الدراسة أن مساحة المسطح الورقي للنبات عند نفس الشد الرطوبي تزداد مع زيادة نسبة الإضافة من الهيومات وكان هذا المسطح أعلى ما يمكن عند 600 ميلليبار ومستوى إضافة 1.8كغ/دونم وبلغ  2476 سم2.   This research was conducted to study the effect of different levels of potassium humate (POWHUMUS WSG 85) (0.6-1.8-3.6 kg/d) at different levels of moisture tension (400-600-800 millibar) on the physical properties of clay silty soil growing maize. The results shows that soil bulk density was significantly decreased at 400 millibar in all levels of potassium humate added by 0.05-0.1-0.17 g/cm3 respectively. Increasing moisture tension to 600 and 800 and not receiving humate, bulk density decreased by 0.08 -0.13 g/cm3 compared to the moisture tension 400 millibar treatment. The experimental constants (a) and (b) in ψ=aθb increased as level of humate addition was increased at all levels of moisture tension. The hydraulic saturated conductivity coefficient increased significantly by 2.71 and 4.17 m/day at moisture tension 400 and 800 millibar respectively, when receiving 3.6 kg humate/d. The percentage of available water in the soil increased at the level of 3.6 kg humate/d by 5.47, 5.33, and 5.14% with increasing moisture tension from 400 to 600 to 800 millibar respectively, compared with the same moisture tension treatments but not receiving humate amendment. The study showed that leaf area of maize plant at the same moisture tension increases with the increase of humate addition reaching the highest value of 2476 cm2 in treatment 600 millibar and the level of humate addition of 1.8 kg/d.